Faktor-Faktor Produksi Dan Konsep Kepemilikan - Muhdi Kholil (LITERASI (Jurnal Ilmu Pendidikan), 2009)
Issues that are fundamentally appointed by Mannan in his book entitled: "Islamic Economic Theory and Practice" in the Islamic economic system in the theory or production concept is the principle of wealth. The concept of economic welfare in Islam consists of an increase in revenues that caused by increasing of production of good material through using resources maximally, both human and objects. Thus, the improvement of production system in Islam not only mean increased revenues that can only be measured in terms of money, but also improvements in the fulfillment of our needs maximally with minimal effort, but still consider the commandments of Islam in consumption.When talking about the concept of ownership, Mannan had been taken ownership based on the Quran and As-Sunnah. In this case, Islam was different from capitalism and communism, because none of them was successful in placing individuals in a mosaic of social harmony. Private property is the foundation of capitalism. In other hand reducing of private property is its abolition is a target of socialist doctrine.